Indications and hemoglobin thresholds for red blood cell transfusion and iron replacement in adults with gastrointestinal bleeding: An algorithm proposed by gastroenterologists and patient blood management experts - Montoro, Miguel; Cucala, Mercedes; Lanas, Ángel; Villanueva, Cándido; Hervás, Antonio José; Alcedo, Javier; Gisbert, Javier P.; Aisa, Ángeles P.; Bujanda, Luis; Calvet, Xavier; Mearin, Fermín; Murcia, Óscar; et al. (Frontiers in Medicine, 2022)
Gastrointestinal (GI) bleeding is associated with considerable morbidity and mortality. Red blood cell (RBC) transfusion has long been the cornerstone of treatment for anemia due to GI bleeding. However, blood is not devoid of potential adverse effects, and it is also a precious resource, with limited supplies in blood banks. Nowadays, all patients should benefit from a patient blood management (PBM) program that aims to minimize blood loss, optimize hematopoiesis (mainly by using iron replacement therapy), maximize tolerance of anemia, and avoid unnecessary transfusions. Integration of PBM into healthcare management reduces patient mortality and morbidity and supports a restrictive RBC transfusion approach by reducing transfusion rates. The European Commission has outlined strategies to support hospitals with the implementation of PBM, but it is vital that these initiatives are translated into clinical practice. To help optimize management of anemia and iron deficiency in adults with acute or chronic GI bleeding, we developed a protocol under the auspices of the Spanish Association of Gastroenterology, in collaboration with healthcare professionals from 16 hospitals across Spain, including expert advice from different specialties involved in PBM strategies, such as internal medicine physicians, intensive care specialists, and hematologists. Recommendations include how to identify patients who have anemia (or iron deficiency) requiring oral/intravenous iron replacement therapy and/or RBC transfusion (using a restrictive approach to transfusion), and transfusing RBC units 1 unit at a time, with assessment of patients after each given unit (i.e., “don’t give two without review”). The advantages and limitations of oral versus intravenous iron and guidance on the safe and effective use of intravenous iron are also described. Implementation of a PBM strategy and clinical decision-making support, including early treatment of anemia with iron supplementation in patients with GI bleeding, may improve patient outcomes and lower hospital costs.